Pencegahan Primer Pada Penyakit Kanker Payudara - Mulawan Umar (Fakultas Kedokteran Universitas Sriwijaya, 2019)
Breast cancer is the most common cancer among women and with high mortality rate also. There is evidence showing the influence of life style and environmental factors on the development of mammary gland cancer (high-fat diet, alcohol consumption, lack of physical exercise), the elimination of which (primary prevention) may contribute to a decrease in morbidity and mortality. The aim of this paper is to review current knowledge and reports regarding primary prevention of breast cancer.